PENGARUH BUDAYA, KEPEMIMPINAN DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. PLN (PERSERO) DISTRIBUSI JAWA TENGAH DAN D.I. YOGYAKARTA DI SEMARANG - Ryan Irtanto; Ari Pradhanawati; Naili Farida (Universitas Diponegoro, 2014)
Each company will always try to improve employee productivity in order to survive, thrive and have a high confidence of parties outside the company. PT. PLN (Persero) Distribution of Central Java and Yogyakarta is one of the state-owned enterprises engaged handles electrical problems Countries. Productivity of research there is still a standard of work that is not being met thus affecting the workload will affect the employee's performance. Specifically culture within the company will be determined by the teamwork, leadership, organizational characteristics, and the applicable administrative process. So with the good influence of corporate culture and leadership quality and strong motivation, it is expected to create a better work productivity.The purpose of this study was to determine the influence of corporate culture, leadership and motivation on employee productivity PT. PLN (Persero) Distribution of Central Java and Yogyakarta.This study uses a type of explanatory research study of employees of PT. PLN (Persero) and Yogyakarta Central DistribusiJawa sampling technique used was simple random sampling technique. This technique is done randomly, with 100 people from HRM employees. The method of analysis used in this study is the analysis of quantitative data.Results reveal that the significant positive and strong cultural influence on the productivity of which is indicated by the regression coefficient of 0.253 and a correlation coefficient of 0.717 and accounted for 51.4 % . Besides significantly positive leadership and a strong influence on the productivity of which is indicated by the regression coefficient of 0.289 and a correlation coefficient of 0.766 and accounted for 58.7 % . It also significantly stronger motivation and a positive effect on the productivity of which is indicated by the value of the regression coefficient of 0.384 and a correlation coefficient of 0.727 and accounted for 52.8 % . While together culture , leadership and motivation positive effect on productivity shown by multiple linear regression of 0.096 for culture , 0.144 to 0.149 for the leadership and motivation , in addition to the strong influence on the productivity of which is indicated by the correlation coefficient of 0.831 , as well as provide a contribution of 69 % .The conclusion of this study is that there is the influence of corporate culture, leadership, and motivation on employee productivity PT. PLN (Persero) Distribution of Central Java and Yogyakarta. Advice, corporate culture in general has been good and in accordance with the existing leadership in the company, but it should be noted again about the need for recognition and praise employees as well as the attention of the leadership so that employees will be more motivated to work.